ØªÙÙÙÙ ØªØ¹ÙÙÙ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© ÙÙÙØ§Ø·ÙÙÙ Ø¨ÙØºØ© Ø£Ø®Ø±Ù - Rahmawati, Rahmawati (AT-TALIM, 2013)
The teaching and learning process of Arabic in the Islamic Senior High School or Boarding School is aimed at developing studentsâ competence in the language such as listening, speaking, reading, and writing.Â  These four skills are, therefore, must be the focus of instruction. This paper aimed at discussing some important points in designing the evaluation.Â  Therefore, teachers need to know the following things such as: (1) the terms dealing with measurement, evaluation or judgement; (2)Â  principles of evaluation; and (3) tools which are used to measure each of the competence above.CopyrightÂ Â©Â 2013 by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v20i3.47